The Emergence of Aspectual Composition in English (Journal of Pedagogical Inventions and Practices, 2022)
This article provides information on the emergence of aspectual composition in English, the main purpose of aspectual composition is to focus on the syntactic relationship of complex devices expressed in language and to determine the semantic result